Resistance to Thyroid Hormone Beta: A Focused Review - Pappa, Theodora; Refetoff, Samuel (Frontiers in Endocrinology, 2021)
Resistance to thyroid hormone (RTH) is a clinical syndrome defined by impaired sensitivity to thyroid hormone (TH) and its more common form is caused by mutations in the thyroid hormone receptor beta (THRB) gene, termed RTHβ. The characteristic biochemical profile is that of elevated serum TH levels in absence of thyrotropin suppression. Although most individuals are considered clinically euthyroid, there is variability in phenotypic manifestation among individuals harboring different THRB mutations and among tissue types in the same individual due in part to differential expression of the mutant TRβ protein. As a result, management is tailored to the specific symptoms of TH excess or deprivation encountered in the affected individual as currently there is no available therapy to fully correct the TRβ defect. This focused review aims to provide a concise update on RTHβ, discuss less well recognized associations with other thyroid disorders, such as thyroid dysgenesis and autoimmune thyroid disease, and summarize existing evidence and controversies regarding the phenotypic variability of the syndrome. Review of management addresses goiter, attention deficit disorder and “foggy brain”. Lastly, this work covers emerging areas of interest, such as the relevance of variants of unknown significance and novel data on the epigenetic effect resulting from intrauterine exposure to high TH levels and its transgenerational inheritance.